Combination Therapy Involving Ear Cartilage Transfer and Suture-Button Suspension Arthroplasty for Symptomatic Thumb Carpometacarpal Joint Arthritis - Usami, Satoshi; Inami, Kohei (Journal of Wrist Surgery, 2019)
We describe the short-term outcomes of combination therapy involving ear cartilage transfer and suture-button suspension arthroplasty for the treatment of symptomatic thumb carpometacarpal joint arthritis. The concept is to reduce joint arthritis by separate independent approaches, which are renewing the damaged joint surface of the trapezium and first metacarpal bone suspension. Autologous ear cartilage is a desirable material for joint resurfacing arthroplasty without postoperative synovitis or infection, and it is expected to prevent bone impingement or recurrent joint arthritis when postoperative suture-button slack or failure unfortunately occurs.
Keywords: thumb carpometacarpal arthritis; ear cartilage; suspension arthroplasty